Cognitive predictors of mental health trajectories are mediated by inferior frontal and occipital development during adolescence - Li, Qingyang; Cao, Miao; Stein, Dan J.; Sahakian, Barbara J.; Jia, Tianye; Langley, Christelle; Gu, Zixin; Hou, Wenjie; Lu, Han; Cao, Luolong; Lin, Jinran; Shi, Runye; et al. (Molecular psychiatry, 2025)
Laboratory studies show brain maturation involves synaptic pruning and cognitive development. Human studies suggest links between early cognitive performance and later mental health, but inconsistencies remain. It is unclear if specific brain regions mediate this relationship, and the molecular underpinnings are not well understood. Here, our longitudinal analyses in both the Adolescent Brain Cognitive Development and IMAGEN cohorts establish inverted U-shaped relationships between baseline executive function and subsequent symptom trajectories in the high-symptom individuals, whose externalizing (n = 963) or internalizing (n = 1762) symptoms exceed a clinical threshold at any point during the follow-up period, but not in the control group (n = 4291). Volumetric changes in the left lateral occipital cortex (LOC) mediated the relationship with externalizing symptoms (outwardly directed behaviors such as aggression), while changes in the right LOC and pars triangularis mediated the relationship with internalizing symptoms (inwardly directed emotional problems such as anxiety). Transcriptomic and genomic findings highlighted synaptic biology and particularly the gene ADCY1, which is implicated in synaptic pruning, as underlying both moderate executive function and its associated brain mediators. Notably, preadolescent cognitive performance predicts late-onset externalizing symptoms and remitting internalizing symptoms with high accuracies (area under the curve: 0.87 and 0.79). Our findings highlight the predictive value of cognitive performance for adolescent mental health trajectories, and indicate how this is mediated by specific brain regions, and underpinned by particular molecular pathways.